Fisioterapia gerontológica: uma nova perspectiva de atuação da fisioterapia no idoso - Silva, Cristina Cristovão Ribeiro da (2011)
Both aging and longevity are decisive phenomena on various fields of personal and social life. Those phenomena, in turn, require the formation of qualified professionals to assist elderly people, like the physiotherapist. There are two ways of dealing with the elderly population: The first is the geriatric physiotherapy , focused on treatment and prevention of aging/old-age diseases; the second one is gerontologic physiotherapy , whose approach, being based on gerontology, involves, besides aging diseases treatment and prevention mode, the utilization of a perspective where the elderly is seen in a integral manner, considering her or his biological, psychological and social aspects. The differentiation is necessary and complex; it has contributed to the delimitation of the central objectives of this dissertation, that is to say, to situate Gerontologic Physiotherapy inside Physiotherapy, as well as to identify the characteristics of assistance in Gerontologic Physiotherapy. The method chosen was qualitative assessment, with exploratory-descriptive profile; for data collection, have been selected case study and participative observation , both longitudinally conducted under the perspective of gerontologic physiotherapy, involving 22 assistances on a female patient, 94 years old, widow, 4 children, housewife, congestive cardiac insufficiency (CCI), pain in the knee. Although specific, the outcomes were significant, involving, among other aspects, what could be called rebirth . Thus, the patient became lady of her desires , re-appropriating herself of the wishing condition, often denied to the elderly, despite the fact that such condition is age-independent. The investigation has demonstrated that whenever the physiotherapist orients her or himself after gerontologic physiotherapy s principles, the outcomes are quite satisfactory for physical, as well as for social, psychological, and existential aspects